2015
DOI: 10.1080/03079457.2015.1044890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the egg transmission and pathogenicity of Mycoplasma gallisepticum isolates genotyped as ts-11

Abstract: Live Mycoplasma gallisepticum vaccines are used for the control of respiratory disease, egg production losses and egg transmission associated with M. gallisepticum infection in long-lived poultry. The first field case of apparent increased virulence and vertical transmission of ts-11, a live M. gallisepticum vaccine, has been reported. In that study a M. gallisepticum isolate from the broiler progeny of ts-11-vaccinated breeders was genotyped as ts-11 by sequence analysis of four different genetic targets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…The clinical picture was obtained from history at submission and/or interviews with field veterinarians. Bird trials confirmed the pathogenicity of two of the isolates (K6212D and K6222B) (9, 32). One reisolate (K5322C-13) was obtained from specific-pathogen-free layer-type chickens at 2 weeks postvaccination with ts-11.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The clinical picture was obtained from history at submission and/or interviews with field veterinarians. Bird trials confirmed the pathogenicity of two of the isolates (K6212D and K6222B) (9, 32). One reisolate (K5322C-13) was obtained from specific-pathogen-free layer-type chickens at 2 weeks postvaccination with ts-11.…”
Section: Methodsmentioning
confidence: 82%
“…gallisepticum isolates from the broilers and their parents were indistinguishable from the ts-11 vaccine strain by the genotyping methods used and were termed “ts-11-like” isolates (9). The epidemiology of the outbreaks, as well as genotyping and pathogenicity results, indicate that an increase in virulence and vertical transmission of ts-11 vaccine occurred and that the ts-11-like isolates were very likely revertants derived from ts-11 vaccine (9, 16, 32). …”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found three MG strains whose DNA banding patterns matched those of the F strain, which was originally a vaccine strain; currently, the F strain can be considered a vaccine or field strain, with nine strains corresponding to untyped wild-type field strains. In the study by Armour and Ferguson-Noel [24], vaccine mycoplasmas failed to colonize bird tissues; however, under field conditions, as in our study, wild strains can compete for receptors of target cells with the vaccine strain TS-11. Most likely, this competition is one of the reasons why this strain was not isolated successfully.…”
Section: Discussionmentioning
confidence: 38%
“…Due to these disorders, it is essential to consider the possible risk of a reversal of pathogenicity when applying the ts+ MS-H strain or other live ts+ vaccines against Mycoplasma spp. In specific-pathogen-free hens vaccinated under laboratory conditions, Armour and Ferguson-Noel [24] and El Gazzar et al [25] demonstrated that the ts+ MG TS-11 strain could revert its thermosensitivity and pathogenicity, cause septicemia, and invade the ovary, thus infecting the eggs.…”
Section: Discussionmentioning
confidence: 99%
“…As mammalian pathogens are transplacental and transferred through breastfeeding, the transovarian pathway seems not to be highly relevant (see for review [87][88][89][90]). In birds, as in fish, however, gonadal infection of both sexes is used to evade the immune system and also to assist transmission to the next generation [91][92][93][94][95]. As regards fish, several pathogens have been found to infect gonads in a few species (see Table 2).…”
Section: Infection Of the Gonad As A Perfect Way To Evade The Immune mentioning
confidence: 99%